The Effect of Non-Performing Loans (NPL) to the Bank Profitability During the Covid-19 Pandemic (Case Study of Buku III Bank in Indonesia) - Rusli*, Moch.; Fitriana, Aning (Universitas Syiah Kuala, 2023)
Bank is a financial institution that functions as a liaison between parties who have excess funds and those who need funds. In creating bank health, it is measured by profitability indicators to see the ability to increase profits, measure effectiveness and efficiency in management. Its profitability can be seen from the value of ROA (Return On Assets) and ROE (Return On Equity). The banking industry has problems in bad debtors which can be seen from the value of NPL (Non-Performing Loan) and this is exacerbated by special conditions that have occurred in recent years, namely the Covid-19 pandemic. So it is necessary to see how the effect of non-performing loans on bank profitability during the Covid-19 pandemic and this study conducted a case study on Buku III banks in Indonesia represented by 7 banks that reported financial data from 2019-2021, namely Bank HSBC Indonesia, Bank Tabungan Negara, Bank DBS Indonesia, Bank Permata, Bank Mega, Bank DKI, and Maybank Indonesia. The results show that the results of the analysis using SPSS version 25, partially non-performing loans represented with NPLs have no effect on the profitability of banks represented with ROA and ROE. Meanwhile, the same condition occurs in the results of the analysis test simultaneously or together with non-performing credit variables, namely NPLs, do not affect bank profitability, namely ROA and ROE.